2017
DOI: 10.3892/mmr.2017.6708
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol postconditioning relieves ischemia/reperfusion injury in axial skin flaps of rats, inhibits apoptosis and alters the MKP-1/ERK pathway

Abstract: Previous studies have suggested that estradiol can reduce the ischemia/reperfusion (I/R) injury in skin flaps. However, the mechanism, particularly the signal pathways involved in this protective effect are not well established. In the current study, an I/R injury model was established in rats to explore the connection between estradiol protection during I/R injury and extracellular signal‑regulated kinase (ERK) signaling. Healthy male Wistar rats were divided into five groups (n=10): Control group (group I), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Choi, D. E. et al revealed that ERK activation was critical against renal I/R injury (Choi et al 2017). Jin, Q. et al also noticed that estradiol mediated ERK pathway via inhibiting MKP-1 expression, reducing the injury of axial flap by I/R (Jin et al 2017). Given these evidences, ERK pathway related molecules, especially MKP-1, might be involved in the mechanism of D-allose in the protective effect of I/R in the skin flap.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Choi, D. E. et al revealed that ERK activation was critical against renal I/R injury (Choi et al 2017). Jin, Q. et al also noticed that estradiol mediated ERK pathway via inhibiting MKP-1 expression, reducing the injury of axial flap by I/R (Jin et al 2017). Given these evidences, ERK pathway related molecules, especially MKP-1, might be involved in the mechanism of D-allose in the protective effect of I/R in the skin flap.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, ERK signal pathway was noticed to be associated with the development of I/R injury (Choi et al 2017;Jin et al 2017). Given these information, we intended to investigate the function of D-allose in skin flap of rat followed by the injury of I/R and whether ERK signal pathway was involved in.…”
Section: Introductionmentioning
confidence: 99%
“…The ERK antagonist PD98059 (MedChemExpress,0.3mg/kg) was diluted in DMSO and PBS and administered intraperitoneally (i.p.) daily [21]. Flu (Aladdin Reagent Shanghai) was solubilized in sterile distilled water and administered intraperitoneally (i.p.)…”
Section: Drug Treatmentmentioning
confidence: 99%
“…daily [21]. Flu (Aladdin Reagent Shanghai) was solubilized in sterile distilled water and administered intraperitoneally (i.p.)…”
Section: Drug Treatmentmentioning
confidence: 99%